Mexico, interrupted : labor, idleness, and the economic imaginary of independence - Gutiérrez Negrón, Sergio, 1986- (Critical Mexican studies., 2023)
"Mexico, Interrupted: Labor, Idleness, and the Economic Imaginary of Independence, 1821-1867 investigates the fate of these economic hopes during the difficult decades between the year of the country's definite separation from Spain and the year of the defeat of the French occupation and the restoration of the Republic, which many took to be the second and final independence of the territory"--